Analisis Hukum Islam terhadap Kebijakan Makan Bergizi Gratis (MBG) di Indonesia dan Dampaknya bagi Masyarakat - Akbar Rizky Subiantoro; Sonny Banda Lubis; Fadly Aulia Hafiz Sitompul; Rayhan Abyasha; Syahzan Harahap (Albayan Journal of Islam and Muslim Societies, 2025)
This study examines the Free Nutritious Meals (MBG) policy in Indonesia through an Islamic legal perspective using a fiqh siyasah approach. This study begins with the urgent role of the state in ensuring public welfare, particularly in meeting basic nutritional needs, which impacts the quality of human resources. This study aims to examine the concept of welfare from an Islamic perspective, examine the legal basis and implementation of the MBG program in Indonesia, and analyze the policy based on the principles of maslahah mursalah and maqasid sharia, particularly in terms of protecting life (hifz an-nafs) and offspring (hifz an-nasl). The method used is qualitative research with a library research approach, analyzed descriptively and analytically using various sources such as the Quran, hadith, fiqh siyasah literature, laws and regulations, and relevant scientific references. The results of the study indicate that the MBG program aligns with the principles of Islamic law because it contains elements of significant maslahah in improving public health, reducing stunting rates, and strengthening social welfare. Thus, the MBG policy can be understood as a form of implementing the government's responsibility in realizing social justice in line with the values of fiqh siyasah.